Analisis Dakhil Dalam Tafsir Jami Al-Bayan ‘An Takwil Ayi Al-Qur’an Tentang Ayat-Ayat Kisah - Ride, Ahmad Rozy Ride; Masruhan; Mohd Zhuhron Azzani (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
The development of the interpretation of the Qur'an includes the interpretation of the meaning contained in the Qur'an, as well as its application and contextualization in everyday life. The product of the interpretation of the Qur'an produced by the mufassir, is not always the same or in harmony with each other. Expertise, tendencies and methods used by mufassirs, become some of the main factors causing differences in interpretation. al-Dakhi>l in the term mufassir, is an interpretation or interpretation that does not have the slightest origin in religion, with the aim of destroying the content of the Qur'an. Therefore, the science of al-dakhi>l is needed to clean and parallelize the Qur'an from things that are not actually from the Qur'an. This study will describe the al-dakhi>l done by one of the mufassirs, Imam Thabari. The research model used, namely qualitative research by applying the type of library research. The results of this study indicate that there are several interpretations of Imam Thabari on the verses of the Qur'an including al-dakhi>l. Especially in the verses about the story in the Qur'an; as well as the use of dha'if hadith, aqwal shahabi, and tabi'in which are dha'if in Surah al-Kahfi; another thing is also found in Surah al-Naml, namely the use of Israiliyyat History.